Effects of palm bunch potash, trona and their modified cashew gum-corn starch composite on the physicochemical properties of furosemide - Ebere I. Okoye; Austinline C. Ekweogu; Ugochukwu E. Oruna (Journal of Pharmacy & Pharmacognosy Research, 2017)
Context: In Nigeria, traditional cuisines are prepared using either palm bunch ash (PBA) or trona to impart emulsification, tenderizing and flavouring attributes to oils, proteins and polysaccharides in delicacies. Hypothesis is that they may improve the solubility and dissolution profiles of poorly soluble and permeable drug as furosemide.